Sociocultural contextualization and substance use disorder (SUD) interventions among Asian Americans - Azahah Abu Hassan Shaari, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The sociocultural realities of Asian Americans have not yet been intensively incorporated into the counseling practice and research field. This paper aims to develop an analytical understanding of the sociocultural of Asian American clients in light of the Model Minority concept, a cultural label that enables public stereotypes to convey oversimplified images of Asian Americans. This conceptual paper will review and analyze a variety of interventions that are culturally congruent with the needs of Asian American clients with substance use disorders (SUD), including Family Systems Therapy and 12-Step Programs. From July 2020 to January 2021, the author of this study conducted a desk-based data collection and analysis of 100 journal articles, government reports, and newspapers to gain an understanding of the sociocultural contextualization of substance use disorders (SUD) interventions among Asian Americans. On a macro level, this paper will enable mental health professionals such as psychologists and social workers to understand how the dominant values and assumptions of American society influence and shape Asian American life experiences. This knowledge is important, as it will allow mental health professionals to engage in social action to bring change that improves the quality of life for Asian American clients, and other marginalized populations across the world.